2019
DOI: 10.1111/hae.13754
|View full text |Cite
|
Sign up to set email alerts
|

From the voices of people with haemophilia A and their caregivers: Challenges with current treatment, their impact on quality of life and desired improvements in future therapies

Abstract: IntroductionHaemophilia A is a chronic disease requiring frequent intravenous infusions of recombinant factor VIII. Previous studies have shown that challenges associated with current treatments may have significant impacts on quality of life (QoL) that are as important as the health outcomes conferred by the therapy. Emerging therapeutic innovations offer the potential to mitigate treatment‐related challenges, and it is therefore important to develop a better understanding of patient and caregiver experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 22 publications
0
44
0
1
Order By: Relevance
“…Haemophilia A (HA), a congenital bleeding disorder characterized by deficiency of coagulation protein factor (F)VIII, has a negative impact on the health-related quality of life (HRQoL) of affected people. [1][2][3] A clinical hallmark of severe HA is recurrent spontaneous bleeds, particularly into joints, and a substantial corresponding impact on physical health and HRQoL. [4][5][6][7][8] Approximately 30% of previously untreated persons with haemophilia A (PwHA) develop one of the most challenging complications of haemophilia treatment: neutralizing alloantibodies (inhibitors) against FVIII, [9][10][11] preventing effective FVIII prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…Haemophilia A (HA), a congenital bleeding disorder characterized by deficiency of coagulation protein factor (F)VIII, has a negative impact on the health-related quality of life (HRQoL) of affected people. [1][2][3] A clinical hallmark of severe HA is recurrent spontaneous bleeds, particularly into joints, and a substantial corresponding impact on physical health and HRQoL. [4][5][6][7][8] Approximately 30% of previously untreated persons with haemophilia A (PwHA) develop one of the most challenging complications of haemophilia treatment: neutralizing alloantibodies (inhibitors) against FVIII, [9][10][11] preventing effective FVIII prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…It induces financial, technical, and educational challenges that considerably impact their quality of life. 60,61 Subsequently, it may affect adherence to prescribed treatments, 62,63 which may lead to an increased risk of bleeding and joint damage. 62 In addition, it has also been shown that frequent bleedings, especially in joints, and their long-term complications, alter the HA patients' and caregivers' health-related quality of life (HRQOL), especially on emotional, social, and physical aspects.…”
Section: Quality Of Life and Adherence To Treatment With Emicizumab Pmentioning
confidence: 99%
“…Alternate mode of administration and longer-lasting treatment effects were identified as being required to overcome the challenges represented by administration of IV infusion, and coordination of treatment schedules. 63 Therefore, no one can deny that the arrival of non-factor therapies such as emicizumab is revolutionizing the landscape of hemophilia.…”
Section: Quality Of Life and Adherence To Treatment With Emicizumab Pmentioning
confidence: 99%
“…Frequent dosing can be a burden for patients and can negatively affect their quality-of-life, potentially resulting in a lack of treatment adherence that can compromise treatment effectiveness 5,6 . Maintaining FVIII trough levels above 1% is associated with a reduction in bleeding rate and so is often a target for prophylactic therapy.…”
Section: Introductionmentioning
confidence: 99%